TEORI BELAJAR KOGNITIF : STUDI KASUS KINERJA PROJEK SEBAGAI UKURAN DIMENSI PROFIL PELAJAR PANCASILA SISWA SMP NEGERI 3 MUARA KOMAM - Abdul Haris (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The application of cognitive learning theory in project performance as a measure of the Pancasila student profile dimension still faces problems. The problem is experienced by students of SMP Negeri 3 Muara Komam. The purpose of the study was to determine the results of project performance as a measure of the Pancasila student profile dimension in project implementation, teachers apply the principles of cognitive learning theory. The research method is qualitative research with respondents teachers, students and principals. Determination of respondents, namely purposive sampling, is based on research objectives. Snowball sampling occurs through the involvement of participants according to respondents. The research procedure begins with researchers compiling instruments and learning devices for integrating cognitive learning principles, implementing research through interview and observation techniques. Data analysis through temporary conclusions and final conclusions that occur during the interview process. The results of the study were obtained from teacher respondents who had prepared, implemented and transmitted project performance by applying the principles of cognitive learning theory, namely meaningful learning. Student respondents have prepared, implemented, and produced the performance of the Pancasila student profile project and principal respondents have facilitated the preparation, implementation and evaluation of the implementation so that students produce project performance as a measure of the Pancasila student profile dimension.